Psychological Motivations of Students for Book Borrowing in Libraries of Higher Vocational Colleges from the Perspective of “Three Comprehensive Education” - Yan, Rong (International Journal of Emerging Technologies in Learning (iJET), 2021)
The innovative “three comprehensive education” model can mobilize the initiatives of students in higher vocational colleges, whose book borrowing behaviors are affected by “three comprehensive education”. This paper mainly studies the psychological motivations of students for book borrowing in libraries of higher vocational colleges from the perspective of “three comprehensive education”. Firstly, the psychological motivations for book borrowing were analyzed in details under the mechanism of “three comprehensive education”. Then, a dataset was created from the mass data on book borrowing and students. The relevant features were compressed as model inputs, aiming to improve model performance and reduce storage cost. Finally, a perception model was constructed to analyze the psychological motivations of students for book borrowing, and used to solve the five-class classification problem based on the directed acyclic graph. Experimental results prove the scientific of the psychological pattern analysis and the effectiveness of the proposed model. The research results provide a theoretical and practical reference for the effect analysis of “three comprehensive education”.